Penerapan Teknologi Tepat Guna Mesin Pengepres Sampah Plastik Sebagai Bahan Baku Daur Ulang - Muharsono; Sri Sutrismi; Desi Rahmawati; Marlena (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tulungagung, 2021)
Abstract The people of Sobontoro in district Boyolangu and Blumbang in district Campurdarat have a very good concern to manage the plastic waste. Their activities aim to help government create the healthy environment. They plan to build the community which is free from the adverse and dangerous effects of plastic waste. The community has formed a Bank of plastic waste to collect plastic waste for many years. What they have done brought a positive thing. The plastic waste which was initially scattered around their house complex collected and pressed to reduce the volume of waste. The well packed and pressed plastic waste can be more valuable and useful as raw material for recycling plastic products with the help of appropriate technology to be implemented in the community. The problems faced by the Bank of plastic waste relating with the insufficient knowledge about the harmful impact of plastic waste on the environment. The next issue deals with the absence of the appropriate technology to press the plastic waste for the sake of the efficiency in the case of the storage of plastic waste and in the distributing the plastic waste to the factory where the waste will be recycled. The method of carrying out the PPTTG activity involves stakeholders, the public and students. The outputs produced are products (the pressing machines of plastic waste), articles published in national journals, the videos, publications in electronic media and intellectual property right (industrial design and copyright). Abstrak Masyarakat Desa Sobontoro Kecamatan Boyolangu dan Desa Campurdarat Kecamatan Campurdarat memiliki kepedulian terhadap pengelolaan sampah plastik dalam mewujudkan lingkungan yang sehat, bebas dari dampak buruk sampah plastik. Masyarakat membentuk kelompok Bank Sampah untuk mengepul limbah plastik sehingga plastik yang awalnya berserakan, dikumpulkan dan dipress untuk mengurangi volume sampah kemudian dimanfaatkan sebagai bahan baku daur ulang produk yang terbuat dari plastik dengan bantuan Teknologi Tepat Guna untuk diimplementasikan pada masyarakat. Permasalahannya, pengetahuan tentang dampak limbah plastik terhadap lingkungan masih terbatas dan belum memiliki teknologi tepat guna mesin pengepress sampah plastic agar efisiensi tempat dan menambah volume pengepulan sampah plastik sehingga dapat menambah pendapatan serta menyediakan lapangan kerja. Metode pelaksanan kegiatan melibatkan pemangku kepentingan, masyarakat dan mahasiswa. Luaran yang dihasilkan adalah produk (mesin pengepres sampah), artikel yang di muat di jurnal nasional, video kegiatan, publikasi di media elektronik dan kekayaan intelektual (desain industri dan hak cipta).